Ù‚Ø¯Ø±Ø© Ø§Ù„Ø·Ù„Ø¨Ø© Ø¹Ù„Ù‰ Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù†ØµÙˆØµ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ø¹Ø§Ù„Ù‰ Ø§Ù„ØªØ±Ø¨ÙˆÙŠ Ø§Ù„Ù‡Ù„Ø§Ù„ Ø³Ø¬Ù„ÙŠ - Teuku Sanwil (Pedir Research Institut, 2023)
This study aims to determine the students' ability to read Arabic texts between graduates of general high schools and Islamic high schools, as well as to identify the differences in the students' ability to read Arabic texts between graduates of general high schools and Islamic high schools. Additionally, it aims to ascertain the factors influencing students' ability to read Arabic texts among graduates of general high schools and Islamic high schools. The research methodology employed by the researcher in this study is the descriptive-analytical method. The research tools utilized for data collection include observation, personal interviews, tests, documents, and questionnaires.The research results indicate that the students' ability to read Arabic texts is high. This is evident from the average score obtained by students from general high schools, denoted as variable 'x,' which is 81.25, corresponding to the